Effects of Deployment Period on Decomposition and Colonization of Leaf Litter of Differing Quality by Invertebrates - Kadeka, Ellen C.; Sitati, Augustine; Kondowe, Benjamin B.; Lusega, David M.; Chirwa, Elias R.; Masese, Frank O. (African Journal of Education,Science and Technology (AJEST), 2021)
Detritivorous invertebrates play major roles in organic matter processing and nutrient cycling in headwater streams. In this study, three common leaf species in upland Kenyan streams (Vernonia myriantha, Syzygium cordatum and the exotic Eucalyptus globulus) were used to determine the influence of deployment period (14 vs 28 days) on relative decomposition rates and colonization by detritivorous invertebrates in headwater streams of the Nzoia River Basin. Leaf decomposition rates were measured by placing 216 litterbags made of coarse- and fine-mesh in six streams draining forested (n =3) and agricultural (n = 3) land-use during the dry months of February- March 2020. For each stream, physico-chemical water characteristics and habitat quality were determined. Measurements of electrical conductivity, pH, temperature, dissolved oxygen concentration and salinity were performed in situ using portable probes. There were no major differences in physical and chemical characteristics between forested and agricultural streams, except for significantly higher canopy cover (p < 0.05) in forested streams, and electrical conductivity and mean water temperature in agricultural streams. Decomposition rates were faster during the first 2 weeks (day 14), and differences between fine- and coarse-mesh litterbags were significant for Vernonia and Syzygium, but not for Eucalyptus. After 14 days, differences between microbial and shredder + microbial breakdown of leaves were clearer than after 28 days, suggesting that short deployment periods (14 days) are enough to establish relative roles of shredders and microbes in leaf litter decomposition experiments in tropical streams. There were inter-specific differences in colonization rates of the leaves by detritivores (shredders) with Vernonia having the highest number of shredder taxa and abundance followed by Syzygium and Eucalyptus. However, there were minimal differences in taxon richness and abundance of shredders and non-shredders between day 14 and day 28. Therefore, this study recommends shorter deployment periods of 14 days rather than long periods of one month or more when studying leaf litter decomposition and colonization by detritivores in tropical streams